Effect of Rare Earth Content on Microstructure and Corrosion Resistance of HRB400 Steel - Chen Hao, Sun Yibin, Xie Qingmin, Liu Xiaolong, Zhang Cunshuai, Peng Zhixian, Cheng Zhaoyang, Liu Jing (Teshugang)
The steel rebar with low cost and excellent corrosion resistance were prepared by adding trace lanthanum （La） and cerium （Ce） rare earth elements. The effect of rare earth addition on the microstructure and corrosion resistance of corrosion resistant steel was studied by means of electrochemical workstation， X-ray diffraction （XRD） and scanning electron microscope （SEM）. The results show that rare earth elements refine the grain size and promote the transformation of MnS and Al2O3 ·SiO2 composite inclusions with long and irregular shape into spherical inclusions （Ce，La） 2O2S with smaller size and more regular shape. Following the addition of rare earth elements， the corrosion potential of the steel shifts positively， while the corrosion current is reduced. Furthermore， rare earth elements contribute to the reduction of unstable γ-FeOOH in the corrosion products， promoting the formation of more stable α-FeOOH， which enhances the stability， compactness， and adhesion of the rust layer. As the rare earth content increases， the corrosion resistance of the steel gradually improves， with the optimal performance observed in the steel containing 0.01% rare earth elements.